1997
DOI: 10.1159/000106633
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Memory in Patients with Mild Alzheimer's Disease

Abstract: Motor, perceptual, and cognitive skill learning abilities of mild Alzheimer''s disease (AD) patients were compared to sex-, age-, and education-matched controls. We excluded patients who were unable to perform each skill learning task with a predetermined criterion. In those who completed the task, skill learning was as good as in normal controls. On the cognitive and perceptual skill learnings, some of the AD patients, whose cognitive but not declarative memory functions were more severely impaired than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 10 publications
3
32
0
4
Order By: Relevance
“…In the same way, in SRTT studies AD patients shown the same amount of learning (decrease in RT during the blocks with the fixed sequence) as the normal controls 56,58,60,61 . The Rotor-Pursuit experiments there were also no patient-control differences in amount of learning [53][54][55][56]58,62,[64][65][66] . Taken together, all studies shown preserved procedural memory in AD patients regardless of the task used.…”
Section: Remaining Performance Level and Amount Of Learning In Ad Patmentioning
confidence: 83%
See 1 more Smart Citation
“…In the same way, in SRTT studies AD patients shown the same amount of learning (decrease in RT during the blocks with the fixed sequence) as the normal controls 56,58,60,61 . The Rotor-Pursuit experiments there were also no patient-control differences in amount of learning [53][54][55][56]58,62,[64][65][66] . Taken together, all studies shown preserved procedural memory in AD patients regardless of the task used.…”
Section: Remaining Performance Level and Amount Of Learning In Ad Patmentioning
confidence: 83%
“…Thus, regardless of task used, the studies assessing Procedural Memory in AD patients and shown positive outcomes. Indeed, hirono et al observed that patients with mild AD were able to acquire motor and perceptual as well as cognitive skills in various motor skills learning tasks 62 .…”
Section: Modulation Of Implicit Learning Capacity Due To Explicit Memmentioning
confidence: 99%
“…It appears that many patients were excluded from several studies that concluded that procedural memory is preserved in AD. For example, Hirono, Mori, Ikejiri, Imamura, Shimomura, Ikeda et al (1997) showed that 11 AD patients out of 20 presented equivalent results to controls on a computerized puzzle task. Knopman and Nissen (1987) proved that AD patients learned the sequence normally in a Serial Reaction Time task; however, we note that 7 patients out of 35 were unable to perform this task.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of this deterioration differs considerably in individual cases and can be accelerated in people with neurodegenerative disorders such as AD [8,16,27,28]. In particular, individuals with AD exhibit a significant behavioral decline or disturbance in their motor and cognitive performance [16,20,27,30]. A recent study of handwriting in AD and MCI patients indicates that a compromised motor performance is the behavioral manifestation of cognitive impairments [44].…”
Section: Sensory-motor Disorders Associated With Agingmentioning
confidence: 99%
“…Furthermore, the prevalence of MCI is twice as high as that of dementia [26]. Given these alarming statistics and the fact that MCI can have negative effects on the quality of life of both individuals with the disorder and their caregivers [20], researchers are becoming increasingly interested in the accurate diagnosis, treatment, and potential rehabilitation of MCI [38,43]. Early detection and treatment of MCI may reduce the risk of conversion to AD or other forms of dementia [1].…”
Section: Introductionmentioning
confidence: 99%